2019
DOI: 10.1186/s12871-019-0914-4
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetics and long-term survival after cancer surgery—total intravenous versus volatile anesthesia: a retrospective study

Abstract: BackgroundIntravenous anesthesia has been reported to have a favorable effect on the prognosis of cancer patients. This study was performed to analyze data regarding the relation between anesthetics and the prognosis of cancer patients in our hospital.MethodsThe medical records of patients who underwent surgical resection for gastric, lung, liver, colon, and breast cancer between January 2006 and December 2009 were reviewed. Depending on the type of anesthetic, it was divided into total intravenous anesthesia … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…There is inconsistent evidence concerning effect of inhalational anesthetic agents on proliferation of cancer [ 2 , 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. There are two main mechanisms by which inhaled anesthetics affect outcomes of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is inconsistent evidence concerning effect of inhalational anesthetic agents on proliferation of cancer [ 2 , 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. There are two main mechanisms by which inhaled anesthetics affect outcomes of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetic methods have a variety of effects on enhancement of pro-tumorigenic cellular signaling, and humoral and cell mediated immunity. These influences could be comprehended an impact of type of anesthetics on long-term prognosis of cancer [ 2 , 14 ]. Reviews of current clinical practice describe that most of anesthesiologists commonly prefer volatile anesthetic agents such as the sevoflurane [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong et al[ 133 ] found that cancer patients treated with volatile inhaled anesthesia had a 5-year overall survival rate similar to those on total intravenous anesthesia. The ENIGMA-II trial did not show negative effects of nitrous oxide on cancer recurrence or mortality[ 134 ].…”
Section: Perioperative Carementioning
confidence: 99%
“… 17 Previous retrospective human studies have shown differing results with some indicating a benefit of propofol-based total intravenous anesthesia versus inhaled volatile anesthesia in cancer surgery, versus others which found no such benefit. 18 - 29 Independent of anesthetic choice, the stress response and inflammation secondary to surgical stimulation appears to increase the likelihood of metastasis and recurrence, which may explain the protective effect of regional anesthesia 7 , 30 , 31 ( Figure 1 ). Opioids appear to be detrimental based on in-vitro and animal studies as a result of decreased NK-cell activity and promotion of angiogenesis by VEGF upregulation.…”
Section: Background and Significancementioning
confidence: 99%